The effectiveness of palm oil clinker (POC) as soil stabilizer - Nur Syazwan , Omar (2012)
Soft soils often cause difficulties in construction, operation with their low strength and low stiffness .nature However, the engineering properties of these soils can be enhanced by soil stabilization. This research was carried out to study the effectiveness of Palm Oil Clinker (POC) as soil stabilizer for soft soil around the area of Pekan,. Pahang. Palm Oil Clinker (POC) was taken from Lepar Huir Palm Oil Mill, Gambang, Pahang. The objectives of this research are to determine the effect of Palm Oil Clinker as soil stabilizer and to propose the optimum percentage of POC to increase the soil characteristics. The soil was classified as clay with very medium plasticity (CV), having liquid limit, plastic limit and plastic index of 315%, 7.3%, and 26.2% respectively, maximum dry density and optimum moisture content of 1 .67gfcm 3 and 7.6% respectively.. There are five laboratory test conducted for this research. Sieve Analysis Test conducted to determine the type of soil. The result from this test shows 74% is silt while remaining 26% is clay proved that this soil is silty clay. Falling Head Test determine the coefficient of permeability for each sample which is for soft soil only is 3.05 x 10 m/s then decreased to 1.08 x 106 in/s when IOC and cement added Atterberg Limit Test conducted to determine PL, LL, and P1. Platicity index for soft soil decreased about 52.4% when POC and cement added. From Standard Proctor Test was applied to determine the maximum dry density and the optimum moisture content of the soils. From this testing, the maximum dry unit weight-was obtained for sample with 5% cement, sample with 5% to 25% POC. and sample with combination 5% cement and 5% to 25% POC. Unconfined Compression Test shows the maximum load can resist by soil. is 66 kPa but increased to 185 kPa when POC and cement added. For overall, addition of POC shows positive result in increasing soil characteristic and soft soil with combination of 5% cement and 25% of POC content shows the effective amount to be added in soft soil stabilization and the objective of this research was achieved.